2011
DOI: 10.1111/j.1439-0507.2011.02081.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of skin adherence and invasion by dermatophytes

Abstract: SummaryDermatophytes are keratinophilic fungi that can be pathogenic for humans and animals by infecting the stratum corneum, nails, claws or hair. The first infection step consists of adherence of arthroconidia to the stratum corneum. The mechanisms and the kinetics of adherence have been investigated using different in vitro and ex vivo experimental models, most notably showing the role of a secreted serine protease from Microsporum canis in fungal adherence to feline corneocytes. After germination of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 53 publications
0
56
2
5
Order By: Relevance
“…Aspartyl and serine peptidases are also associated with dermatophyte fungi, which infect the stratum corneum, nails, and hair of animals; here, they are implicated in promoting adherence to host cells and degradation of keratin during tissue invasion (17,18). Both Candida species and dermatophytes display expanded protein families of peptidases, supporting the idea that these molecules are key virulence factors (15,18).…”
mentioning
confidence: 88%
“…Aspartyl and serine peptidases are also associated with dermatophyte fungi, which infect the stratum corneum, nails, and hair of animals; here, they are implicated in promoting adherence to host cells and degradation of keratin during tissue invasion (17,18). Both Candida species and dermatophytes display expanded protein families of peptidases, supporting the idea that these molecules are key virulence factors (15,18).…”
mentioning
confidence: 88%
“…Dissemination of dermatophytes depends on direct or indirect contacts between infected and uninfected hosts. The first step in the infection process corresponds to colonisation of the cornified layers of the SC [3,4]. Fungal cells representing the contagious and infectious propagules correspond to arthroconidia and hyphal fragments adhering to, or contained within some corneocytes.…”
Section: Dermatomycoses In the Immune Compromised Patientmentioning
confidence: 99%
“…This is the crux of the problem of infections in immunocompromised patients. The adhesion of microorganisms to the stratum corneum (SC) [3,4], and its barrier system represent additive components of the skin protection. …”
Section: Introductionmentioning
confidence: 99%
“…With the exception of direct inoculation of the nail plate, tinea pedis precedes DLSO onychomycosis. Studies have shown concurrent active tinea pedis in the majority of onychomycosis cases; undoubtedly, the remaining cases either had treated tinea pedis or non-DLSO subtypes 4-7 Dermatophytes invade the stratum corneum via keratinolytic proteases with hyphae growing in multiple directions [10,11]. Left untreated (or only partially treated), the infection extends from the plantar surface to the distal nail bed causing DLSO [12].…”
Section: Tinea Pedis Overview and Relationship To Onychomycosismentioning
confidence: 99%